Medicinal Plants from North and Central America and the Caribbean Considered Toxic for Humans: The Other Side of the Coin. (2nd November 2017) - Alonso-Castro, Angel Josabad; Domínguez, Fabiola; Ruiz-Padilla, Alan Joel; Campos-Xolalpa, Nimsi; Zapata-Morales, Juan Ramón; Carranza-Alvarez, Candy; Maldonado-Miranda, Juan Jose
Abstract : The consumption of medicinal plants has notably increased over the past two decades. People consider herbal products as safe because of their natural origin, without taking into consideration whether these plants contain a toxic principle. This represents a serious health problem. A bibliographic search was carried out using published scientific material on native plants from Mexico, Central America, and the Caribbean, which describe the ethnobotanical and toxicological information of medicinal plants empirically considered to be toxic. A total of 216 medicinal plants belonging to 77 families have been reported as toxic. Of these plants, 76 had been studied, and 140 plants lacked studies regarding their toxicological effects. The toxicity of 16 plants species has been reported in clinical cases, particularly in children. From these plants, deaths have been reported with the consumption of Chenopodium ambrosioides, Argemone mexicana, and Thevetia peruviana . In most of the cases, the principle of the plant responsible for the toxicity is unknown. There is limited information about the toxicity of medicinal plants used in Mexico, Central America, and the Caribbean. More toxicological studies are necessary to contribute information about the safe use of the medicinal plants cited in this review.